2020
DOI: 10.3390/app11010329
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Fall Detection Based on OpenPose Skeleton and LSTM/GRU Models

Abstract: Falling is one of the causes of accidental death of elderly people over 65 years old in Taiwan. If the fall incidents are not detected in a timely manner, it could lead to serious injury or even death of those who fell. General fall detection approaches require the users to wear sensors, which could be cumbersome for the users to put on, and misalignment of sensors could lead to erroneous readings. In this paper, we propose using computer vision and applied machine-learning algorithms to detect fall without an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…The results showed the high accuracy of body part detection of the human for multi-person detection. Lin et al [46] also deployed the OpenPose method to detect human movement through detecting the keypoints of human joint changes. They applied the series recurrent neural network, long-and short-term memory (LSTM), and gated recurrent unit (GRU) models to detect a human fall.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…The results showed the high accuracy of body part detection of the human for multi-person detection. Lin et al [46] also deployed the OpenPose method to detect human movement through detecting the keypoints of human joint changes. They applied the series recurrent neural network, long-and short-term memory (LSTM), and gated recurrent unit (GRU) models to detect a human fall.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…From our own review, we conclude that OpenPose is the one that has generated more literature works and seems to have the largest community of developers. OpenPose has been used in multiple areas: sports [87], telerehabilitation [88], HAR [89][90][91], artistic disciplines [92], identification of multi-person groups [93], and VR [94]. Thus, we have selected OpenPose algorithm for this work due to the following reasons: (i) it is open source, (ii) it can be applied in real situations with new video inputs [84], (iii) there is a large number of projects available with code and examples, (iv) it is widely reported in scientific papers, (v) there is a strong developers community, and (vi) the API gives users the flexibility of selecting source images from camera fields, webcams, and others.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have revealed that an RNN has been implemented in the development of fall classification systems. The work by Lin et al [ 21 ] employed the RNN architecture using LSTM as the underlying model to capture temporal relationships of the body joints, which were pre-extracted using OpenPose. LSTM classifies the fall features from the non-fall features based on the change trajectory of the extracted body joint points.…”
Section: Related Workmentioning
confidence: 99%
“…Recent research trends have grouped fall event detection techniques based on the type of sensor. The three categories are as follows: wearable devices [12][13][14][15][16], ambientbased devices [17][18][19], and vision-based sensors [20][21][22][23]. Both wearable and ambient-based devices require the sensors to be in close proximity to the targeted users.…”
Section: Introductionmentioning
confidence: 99%